THE EFFECT OF LONG-TERM PATELLAR TENDINOPATHY INJURY ON VERTICAL JUMP ABILITY IN HIGH SCHOOL BASKETBALL PLAYERS NEG. 2 PEMATANGSIANTAR - Isaharpika Br Ginting; Yeni Trisna Purba; Ruth Mala Livia Theola Lumbantoruan (Mount Hope Economic Global Journal, 2025)
This research aims to determine the effect of long-term injury of patellar tendinopathy on the ability of vertical jumps in basketball athletes. Method: this research is quantitative descriptive with the type of correlation study. Samples were selected using a purposive sampling technique. The sample consisted of 18 male and female basketball players from the Shoots Hope club with the age category of 16 years to 23 years, with inclusion criteria. Still actively participating in training conducted by Tunas Harapan basketball club. Having a history of patellar tendinopathy or having a recurrent patellar tendinopathy injury, at least 1 month. where the duration of tendinopathy injury is measured using a questionnaire and the vertical jump ability test is measured using a sargent test. Results: The mean and standard deviation of the length of time for patellar tendinopathy injuries was 3.89 ± 2.74 calculated in months and the average vertical jump and standard deviation were 45.21 ± 8.46 calculated in centimeters. Normality test with Shapiro Wilk test obtained data with normal distribution. The results of hypothesis testing with Spearman rank correlation test showed p = 0.005 on injury time and vertical jump test and r = -0.718 with negative direction so the longer the injury the more it affects the ability of vertical jump in basketball athletes. Conclusion: There is a long-standing relationship of patellar tendinopathy injury to the ability of vertical jumps in basketball athletes.